Incidence of non-age-dependent chromosomal abnormalities: a population-based study on 88965 amniocenteses - Forabosco, Antonino; Percesepe, Antonio; Santucci, Sandra (European journal of human genetics : EJHG, 2009)
Current knowledge about the incidence of chromosomal abnormalities in the general population comes from studies in newborns carried out in the 70s, before the era of widespread prenatal diagnosis. In the following years, data on frequency of chromosomal abnormalities in the second trimester of pregnancy have been used in conjunction with the data on the natural history of chromosomally abnormal fetuses to infer maternal age-specific rates of cytogenetic abnormalities in live-born infants. Starting from the data gathered in 1995–1996 from all Italian cytogenetic laboratories (with 92% compliance to the study), we have compared the frequency of chromosomal abnormalities at amniocentesis in cases with maternal age of ≥35 years (51 758 individuals) and cases with maternal age of <35 years (37 207 cases). The comparison confirmed the age-dependency of aneuploidies, whereas none of the structural abnormalities showed age-related differences. Furthermore, among the mosaic aneuploidies, trisomy 21 and 45,X/46,XX were found with a significantly higher incidence in older women. Chromosomal abnormalities that showed no significant difference between the two groups were summed for the overall national cohort, providing a general estimate of the incidence in the second trimester of pregnancy. The data provide critical background information for prenatal genetic counseling and for the planning of health care policy.